Lower bounds of Nikiforov’s energy over digraphs (2016)
The energy of a graph G is defined as E(G) = |λi|, where λ1, λ2, ..., λn are the eigenvalues of the adjacency matrix of G. This concept was extended by Nikiforov to digraphs as N (D) = n i=1 σi, where D is a digraph with n vertices and singular values σ1, ..., σn. Upper bounds of N were found by Kharaghani and Tayfeh-Rezaie. In this work we find lower bounds of N over the set of digraphs.